Transport phenomena in helical edge state interferometers: A Green's function approach - Rizzo, Bruno (2013)
We analyze the current and the shot noise of an electron interferometer made of the helical edge states of a two-dimensional topological insulator within the framework of nonequilibrium Green´s functions formalism. We study, in detail, setups with a single and with two quantum point contacts inducing scattering between the different edge states. We consider processes preserving the spin as well as the effect of spin-flip scattering. In the case of a single quantum point contact, a simple test based on the shot-noise measurement is proposed to quantify the strength of the spin-flip scattering. In the case of two single point contacts with the additional ingredient of gate voltages applied within a finite-size region at the top and bottom edges of the sample, we identify two types of interference processes in the behavior of the currents and the noise. One such process is analogous to that taking place in a Fabry-Pérot interferometer, while the second one corresponds to a configuration similar to a Mach-Zehnder interferometer. In the helical interferometer, these two processes compete.